(untitled) (Jurnal Pilar Nusa Mandiri, 2024)
The current implementation of smart cities aims to enhance the quality of life for their communities. Smart city investments can be achieved through collaborative efforts between information and communication technology and human resources, transforming areas into sustainable cities. Many countries are becoming increasingly interested in smart city investments. However, it remains unclear how these investments can achieve their intended goals. The primary issue lies in the lack of effective methodologies to measure the economic impact of such investments. Many cities lack comprehensive assessment tools to gauge the economic impact of smart city implementations, making it difficult to determine whether these investments deliver the desired benefits. This article aims to provide references regarding the economic impacts of smart city investments and the frameworks that can be used to measure them. The methodology employed in this research is a literature review based on references published over the past five years. According to findings, smart city investments have been found to impact aspects such as e-commerce and e-business, the creation of environmentally friendly environments, cost savings and economic benefits, GDP growth, and increased income for regions/cities through effective smart city utilization. Several frameworks have been gathered to measure economic impact, such as Computable General Equilibrium (CGE), Energy Efficient Integrated Planning Framework (EEIPF), and Open Data Impact for Smart Cities Framework (ODISC). Each framework serves to illustrate how examples of smart city investments can influence the economy of a region or city.